2023
DOI: 10.12681/mms.27391
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopes provide evidence of a trophic shift in the lesser spotted dogfish Scyliorhinus canicula from the Central Tyrrhenian Sea

Abstract: Stable isotopes (δ13C and δ15N) were analysed in vertebrae of Scyliorhinus canicula (n=40; 13 males, 27 females) from the central Tyrrhenian Sea to explore a potential trophic shift in relation to sex and maturity condition. Isotopic values were obtained from the centre and the periphery of the vertebra of each individual to test for the effect of maturity condition. The values of δ13C and δ15N showed significant differences between the immature and mature state of the individuals analysed (U’=1392, P<0.000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This trend is well-known in fishes [54,55]. In S. canicula, this may be sustained by a growth-related change of the diet [17] and the higher detoxifying activity of the rectal gland observed in relation to animal growth (and the consequent increase in TL) that may contribute to excrete some toxic trace elements, as in the case of Pb [45,46]. Of note, in the skeletal muscle, the levels of Mn and Zn significantly and negatively correlated with the leukocyte count.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…This trend is well-known in fishes [54,55]. In S. canicula, this may be sustained by a growth-related change of the diet [17] and the higher detoxifying activity of the rectal gland observed in relation to animal growth (and the consequent increase in TL) that may contribute to excrete some toxic trace elements, as in the case of Pb [45,46]. Of note, in the skeletal muscle, the levels of Mn and Zn significantly and negatively correlated with the leukocyte count.…”
Section: Discussionmentioning
confidence: 55%
“…This different sex ratio is not unusual in sharks, being possibly related to the breeding behavior of the species. For example, unisexual aggregations of S. canicula have been observed in certain geographical areas and at different times of the year [17,29,42,43]. The biometric analysis of the samples used in this study showed no significant differences between males and females in terms of length and weight.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Sharks are mostly long-lived elasmobranch species and occupy apex-meso-predator roles in their respective food webs (e.g., [25]). Therefore, they are known to accumulate high levels of metals, metalloids, and other pollutants in their tissues [26][27][28]. This feature results in deleterious effects on their normal physiology/biochemistry (e.g., immune and endocrine toxicity, reproductive deficits and tumor promotion) and ultimately on shark population dynamics [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…This demersal elasmobranch species can be found widespread throughout the Mediterranean and north-eastern Atlantic´s continental platform and the upper slopes (Ebert and Stehmann, 2013;Kousteni et al, 2015;Massutí and Moranta, 2003;Ruiz-García et al, 2023;Serena et al, 2020). This opportunistic predator´s diet has been found to be highly generalistic, being comprised mainly of crustaceans, molluscs, and teleosts (Barría et al, 2017;Kousteni et al, 2017;Lyle, 1983;Reinero et al, 2023;Valls et al, 2011). S. canicula captures are a common occurrence among Mediterranean sheries within which, adults are occasionally targeted by shermen due to their greater economic value, while younger individuals are generally discarded at sea (Barausse et al, 2014;Capapé et al, 2008;Carbonell et al, 2003).…”
Section: Introductionmentioning
confidence: 99%